The Ethics of Carbon Neutrality: A Critical Examination of Voluntary Carbon Offset Providers - Dhanda, K. Kathy; Hartman, Laura P. (2011)
In this article, we explore the world’s response to the increasing impact of carbon emissions on the sobering threat posed by global warming: the carbon offset market. Though the market is a relatively new one, numerous offset providers have quickly emerged under both regulated and voluntary regimes. Owing to the lack of technical literacy of some stakeholders who participate in the market, no common quality or certification structure has yet emerged for providers. To the contrary, the media warns that a relative “cowboy” atmosphere prevails in the current environment, and that there are “widespread instances of people and organizations buying worthless credits that do not yield any reductions in carbon emissions” (Harvey and Fidler, Financial Times, 2007). At this point in the evolution of the market, only a handful of offset provider-rating schemes exist; and, even these systems leave consumers with few answers when they seek to find a means by which to ensure that the said systems are having their intended impact. The purpose of this article is, first, to provide a grounded understanding of the nature of the offset market, a tendency toward carbon neutrality as a possible point of equilibrium, and the ethical tensions that surround it from the perspective of the consuming public. Second, we outline the standards environment for offset providers to illustrate most effectively the need for a single set of criteria among providers that is readily understandable by the common consumer stakeholder. We then explore the differences among the providers and articulate the specific criteria upon which providers may be evaluated by this particular stakeholder constituency, by bringing together best practices based on currently available analyses. Finally, we share the results of preliminary data collection in connection with 117 offset providers and highlight early findings. These findings allow us comparing providers effectively and efficiently on a common scale that services both providers, who thereby have greater guidance for self-assessment purposes, as well as consumer stakeholders, who then have the ability to make useful and more informed choices about carbon emission reduction in the future.
Keywords: Sustainability; Ethics; carbon neutrality; offsets; Global warming; Carbon emissions